(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the concept, content, and main tasks of ensuring the rational use of natural resources from a legal and socio-ecological perspective. Particular attention is given to the role of environmental law, sustainable development principles, and state regulatory mechanisms in preserving natural resources. The study highlights the importance of balancing economic development with environmental protection and outlines the main directions for improving legal frameworks in this sphere.